Differential Diagnosis of Flavivirus Infections in Horses Using Viral Envelope Protein Domain III Antigens in Enzyme-Linked Immunosorbent Assay - Piyasena, Thisun B.H.; Setoh, Yin X.; Peters, Jody Hobson; Prow, Natalie A.; Ohmann, Helle Bielefeldt; Khromykh, Alexander A.; David, Perera; Cardosa, Mary Jane; Kirkland, Peter D.; Hall, Roy A. (Mary Ann Liebert, Inc., 2017)
In Australia, infection of horses with the West Nile virus (WNV) or Murray Valley encephalitis virus (MVEV) occasionally results in severe neurological disease that cannot be clinically differentiated. Confirmatory serological tests to detect antibody specific for MVEV or WNV in horses are often hampered by cross-reactive antibodies induced to conserved epitopes on the envelope (E) protein. This study utilized bacterially expressed recombinant antigens derived from domain III of the E protein (rE-DIII) of MVEV and WNV, respectively, to determine whether these subunit antigens provided specific diagnostic markers of infection with these two viruses. When a panel of 130 serum samples, from horses with known flavivirus infection status, was tested in enzyme-linked immunosorbent assay (ELISA) using rE-DIII antigens, a differential diagnosis of MVEV or WNV was achieved for most samples. Time-point samples from horses exposed to flavivirus infection during the 2011 outbreak of equine encephalitis in south-eastern Australia also indicated that the rE-DIII antigens were capable of detecting and differentiating MVEV and WNV infection in convalescent sera with similar sensitivity and specificity to virus neutralization tests and blocking ELISAs. Overall, these results indicate that the rE-DIII is a suitable antigen for use in rapid immunoassays for confirming MVEV and WNV infections in horses in the Australian context and warrant further assessment on sensitive, high-throughput serological platforms such as multiplex immune assays.